Detection of infectious bronchitis virus and specific anti-viral antibodies using a concanavalin A-Sandwich-ELISA - Bronzoni, RVM; Fatima, M.; Montassier, S.; Pereira, G. T.; Gama, NMSQ; Sakai, V; Montassier, H. J. (Mary Ann Liebert, Inc., 2005)
Concanavalin A-Sandwich ELISA (Con A-S-ELISA) was developed for the detection of infectious bronchitis virus (IBV) or chicken specific anti-viral antibodies. The antigen detection limit for the Con A-S-ELISA was 10(5,1) EID50/mL. Three homologous and four heterologous IBV strains were similarly detected. This assay was highly effective in detecting the virus after infected tissue homogenates were passed once in embryonated chicken eggs, showing a good agreement with virus isolation technique. The Con A-S-ELISA was also used to measure anti-IBV chicken antibodies and showed a high coefficient of correlation (r = 0.85) and an agreement of k = 0.80 with the commercially available Indirect-ELISA. The relative sensitivity and specificity between these two tests were, respectively, 92.86% and 95.65% with an accuracy of 93.39%. Thus, the Con A-S-ELISA proved to be able to detect alternatively homologous and heterologous IBV strains or specific chicken anti-IBV antibodies, using the Con A as capture reagent of this assay.